1989
DOI: 10.1111/j.1600-0773.1989.tb00652.x
|View full text |Cite
|
Sign up to set email alerts
|

An Open Field Study of Antidepressant Drugs

Abstract: Eight psychotropic drugs, mainly acting on the catecholaminergic systems, were investigated in an open field setting. All drugs but one showed a significant reduction in overall activity over time. Only piribedil at 32 mg/kg showed an increase, while 2 mg/kg showed a decrease over time. Amineptine and nomifensine significantly increased and salbutamol significantly decreased both ambulation and rearing with dose. For viloxazine, metapramine, piribedil and piracetam no significant dose effects were revealed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…However, other mechanisms could potentially explain the changes in motor behavior we observed after MGE cell transplantation. Our results are similar to those showing that L-dopa administration increases open field activity levels in control rats (Dahl and Götestam, 1989; Ljungberg and Ungerstedt, 1976). Thus, it is also possible that the transplantation of MGE cells induced secondary changes in the striatum that produced or contributed to the behavioral changes (Goto et al, 1997).…”
Section: Discussionsupporting
confidence: 92%
“…However, other mechanisms could potentially explain the changes in motor behavior we observed after MGE cell transplantation. Our results are similar to those showing that L-dopa administration increases open field activity levels in control rats (Dahl and Götestam, 1989; Ljungberg and Ungerstedt, 1976). Thus, it is also possible that the transplantation of MGE cells induced secondary changes in the striatum that produced or contributed to the behavioral changes (Goto et al, 1997).…”
Section: Discussionsupporting
confidence: 92%
“…It has been demonstrated that NPY modulates the release of dopamine via an NPY Y 2 receptor controlled mechanism (Ault and Werling 1997). In addition, dopamimetics have been shown to display antidepressant-like activity in the forced swimming test (Willner 1997), as well as increased activity in the open field (Dahl and Gotestam 1989). As there is little or no behavioral data published to date using BIIE0246, a full and more detailed psychopharmacological profile of this molecule is warranted before any firm conclusions can be made.…”
Section: Discussionmentioning
confidence: 99%
“…In open ®eld studies in rats, amineptine and nomifensine show a dose dependent activating effect (Dahl and Gotestam, 1989). Misuse of dothiepin and amitriptyline to produce sedation or euphoria has been reported in patients receiving methadone maintenance (Cohen et al, 1978;Cantor, 1979;Dorman et al, 1995).…”
Section: Pharmacological Issuesmentioning
confidence: 99%